The use of digital internal communications for operational excellence: A case study of African Rainbow Minerals (ARM) - Maloka, Mologadi Betty (University of the Witwatersrand, Johannesburg, 2024)
This research paper employs a qualitative research methodology with a deductive approach to investigate the impact of digital internal communication on operational excellence, using African Rainbow Minerals (ARM) as a case study. The study recognises employees as primary stakeholders, contending that well- informed employees contribute to heightened productivity. Digital communication, facilitating information exchange and team collaboration, plays a pivotal role in the workplace. The study explores the use of digital communication tools for internal communication, customer interaction, teamwork, and overall productivity enhancement. Digital internal communication tools streamline feedback, idea expression, and collaboration, fostering a conducive environment for meaningful employee engagement. Effective internal communication is crucial for organisational culture, work enthusiasm, and stability during turbulent periods. The adoption of key elements in digital workplaces, including inclusion, reinvention, employee empowerment, and technological balance, is essential for achieving operational excellence. The study reveals that ARM employees primarily use four digital tools for improved collaboration and communication. However, challenges like resistance to change and poor system implementation hinder communication system objectives. The research and proposed model underwent experts’ evaluation for constructive feedback. The study emphasises the importance of aligning digital communication strategies with organisational goals, promoting inclusivity, and fostering adaptability. Integrating these recommendations into ARM's digital transformation strategy can lead to a more connected and agile workforce, enhancing operational excellence in the mining industry. The study concludes that digital communication is crucial for operational excellence but requires mutual understanding among key stakeholders in implementing digital tools
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital Communication; Digital platforms; Digital Technology; Digital Transformation; Internal Communication; Operational Excellence; UCTD; SDG-8: Decent work and economic growth